Empowerment Teachers of SMA Malang Raya Making Eco Enzyme and Biology Module for Teachers of SMA Malang Raya - Balqis Balqis; Herawati Susilo; Murni Saptasari3; Sitoresmi Prabaningtyas4; Ringga Satria Putra; Iin Lailatul Khoirunnisa; , Rifqi Hilman (Community Development Journal, 2023)
The 21st century is characterized by information that can be accessed by anyone, anytime and anywhere, computing or using robots, automation or work that can be done regularly and communication that becomes unlimited. Educators are required to be able to facilitate and inspire student learning and creativity, such as involving students in exploring real-world issues and solving contextual problems using tools and digital resources. Learning in the form of environmental care needs to be related to the application in students' daily lives in the family, community, and surrounding nature, so that learning becomes meaningful for students. Eco-enzyme is one of the sources and learning media in the surrounding environment that can be raised in the learning process. This can be used as a teaching module that teachers use as innovation. This activity aims to hold eco-enzyme training and the preparation of teaching modules for Biology Teachers of Malang Raya High School. This activity is carried out using the eco-enzym making training method and the preparation of teaching module making exercises by lifting eco-enzymes. The targets of this activity are teachers from malang city and malang district with 15 of them. The results of this activity found that 80% of this activity was successful because it exceeded the target with details of 18 attending offline and 5 attending online. Another thing is shown by the collection of 6 teaching modules.